Visual basic .net for students. - Bell, Doug (Douglas), 1944-; Parr, Mike, 1949- (Harlow : Addison-Wesley, 2003)
Samenvatting:Approaches Visual Basic .NET with a simple and direct style, providingmaximum clarity on the subject without requiring readers to have anyprior knowledge of programming. For anyone, including softwareprogrammers interested in learning about VB.NET. Softcover.
CDrom included
Keywords: Visual basic (programmeertaal).